Estimated and real durability of unfired clay bricks: Determining factors and representativeness of the laboratory tests. (30th January 2017) - Seco, A.; Urmeneta, P.; Prieto, E.; Marcelino, S.; García, B.; Miqueleiz, L.
Highlights: Mechanical resistance depends on the type of the additive but not on the sand content. Capillarity absorption test is not appropriated to estimate earth based construction materials real durability. The total water absorbed test is suitable as earth based construction materials durability estimator. The freeze/thawing cycles test as it is defined in the Spanish Standards is not a good durability estimator. PC-8+GGBS additive obtained the best laboratory and real durability results. Abstract: This paper presents an analysis of the representativeness of the main laboratory tests and the real durability of earth-based construction materials. For this study, a natural marl soil, mixed with different percentages of silica sand, was treated with portland cement, hydraulic lime, a mix of lime and ground granulated blastfurnace slag and other binder composed of a high magnesium oxide waste mixed with ground granulated blastfurnace slag. All the combinations were characterized based on the usual durability related laboratory tests as are: maximum density, unconfined compressive strength, wetting and drying, Swinburne accelerated erosion resistance, capillarity water absorption, total water absorption and freeze/thawing cycles. The results of these tests have been related to the real durability of the samples for eighteen months of outdoor exposure. They revealed the positive effect of sand adding in the materials durability and the great result of the binder based on magnesium oxide with ground granulated blastfurnace slag. It was also demonstrated the representativeness of the water absorption test as a durability indicator of earth based construction materials durability.